2014
DOI: 10.1097/ccm.0000000000000398
|View full text |Cite
|
Sign up to set email alerts
|

Statins and Delirium During Critical Illness

Abstract: Objective Since statins have pleiotropic effects on inflammation and coagulation that may interrupt delirium pathogenesis, we tested the hypotheses that statin exposure is associated with reduced delirium during critical illness whereas discontinuation of statin therapy is associated with increased delirium. Design Multicenter, prospective cohort study. Setting Medical and surgical intensive care units (ICUs) in two large tertiary care hospitals in the United States. Patients Patients with acute respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 54 publications
2
30
1
Order By: Relevance
“…The findings that rosuvastatin did not improve delirium in intensive care conflicts with two rigorous observational studies, 19,20 which showed strong and consistent associations between statin use and reduced daily delirium in intensive care, particularly for patients with sepsis early in their stay in intensive care. 19 The high overall prevalence of delirium in our study or heterogeneity in baseline risk for delirium within our study cohort might have affected our results.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…The findings that rosuvastatin did not improve delirium in intensive care conflicts with two rigorous observational studies, 19,20 which showed strong and consistent associations between statin use and reduced daily delirium in intensive care, particularly for patients with sepsis early in their stay in intensive care. 19 The high overall prevalence of delirium in our study or heterogeneity in baseline risk for delirium within our study cohort might have affected our results.…”
Section: Discussioncontrasting
confidence: 56%
“…19 The high overall prevalence of delirium in our study or heterogeneity in baseline risk for delirium within our study cohort might have affected our results. Additionally, the differences between our findings and those of observational studies might be a result of unmeasured confounders biasing the observational studies—a limitation minimised in a randomised, double-blind trial.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations